3(5c-1)=4(3c+2)

Simple and best practice solution for 3(5c-1)=4(3c+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5c-1)=4(3c+2) equation:


Simplifying
3(5c + -1) = 4(3c + 2)

Reorder the terms:
3(-1 + 5c) = 4(3c + 2)
(-1 * 3 + 5c * 3) = 4(3c + 2)
(-3 + 15c) = 4(3c + 2)

Reorder the terms:
-3 + 15c = 4(2 + 3c)
-3 + 15c = (2 * 4 + 3c * 4)
-3 + 15c = (8 + 12c)

Solving
-3 + 15c = 8 + 12c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-12c' to each side of the equation.
-3 + 15c + -12c = 8 + 12c + -12c

Combine like terms: 15c + -12c = 3c
-3 + 3c = 8 + 12c + -12c

Combine like terms: 12c + -12c = 0
-3 + 3c = 8 + 0
-3 + 3c = 8

Add '3' to each side of the equation.
-3 + 3 + 3c = 8 + 3

Combine like terms: -3 + 3 = 0
0 + 3c = 8 + 3
3c = 8 + 3

Combine like terms: 8 + 3 = 11
3c = 11

Divide each side by '3'.
c = 3.666666667

Simplifying
c = 3.666666667

See similar equations:

| 4v^2=-11v-6 | | 6n-2=4n+6 | | 3x(x+5)= | | 2x^2-20x=-42 | | y+5+2y= | | 6x+5x=63 | | 4(n-1)=-8 | | y^2+9y=-20 | | 5y-2(y+4)=1 | | 3x^2-8x^7-2x^2=9x^7 | | 6x^2-8x-12=0 | | 2K(K+3)=-9 | | 2K(K+3)=9 | | 3(x-4)+15=2(x+3) | | 6y^2-6=0 | | 5/12-7/8= | | 4x^2=4x | | -1/5-4(m+1/12)=39/10(m-11/6) | | a^2b^2-121=0 | | 9+-10x+x^4=0 | | x+6x-40=0 | | -10x+3+9x=-x-7 | | x^4-10x+9=0 | | 5v^3-65v^2+200v=0 | | 2x-7/3=-7 | | 8a+a= | | 6a+12=2a-6 | | 8a-3b+2a+6b= | | 3y+5y=9y | | m^2+9m+7=-5+9(-5)+7 | | 5x^2+10x=40 | | w^2+7w=8 |

Equations solver categories